(untitled) (Balneo and PRM Research Journal, 2024)
Present study aims for the QoL assessment after performing a physiotherapeutic program for lower limbs rehabilitation using a stationary bicycle. Subjects are outpatients, n=7, mean age 51.86 ± 11.82, BMI (kg/m2) mean of 29.37±6.43. Before the beginning of the rehabilitation program (T0) was the first evaluation with RAND SF-36 version 1 and after eight weeks of physical therapy the second one (T2). QoL measurements assessment implies eight criteria. Appropriateness - the main objective of gait facilitation was fulfilled for all seven patients. Acceptability- response rates T0/T2 = 100%. Feasibility - SF-36 OrthoToolKit is licensed (Optum) and available freely online, with a completion time of 6 min in the kit tool. Validity was proved by specialty literature. Reliability Intraclass correlation coefficient - ICC (Cronbach’s Alpha overall test-retest, patient/physical therapist T0/T2 =0.995/1.000) Pearson correlation coefficient between items - strong statistical significance (p<.05). Responsiveness The T-test for paired samples, Wilcoxon, Sign Test resulted significant (p<.05) for each subsequent scale. Effect size (Partial Eta Squared) based on z-score η2 = .432 physical components and .534 mental components – large effect. Precision- based on Likert response. Interpretability - Romanian version was used. QoL outcomes measuring eight criteria proved a positive impact of the intervention on patients.